Cloning, expression and purification of human fibroblast growth factor 21 in Escherichia coli and Pichia pastoris / Farnaz Emamdoust - Farnaz , Emamdoust (2018)
Fibroblast Growth Factor 21 (FGF21) is a novel target with potential anti diabetic properties that are useful for treatment of hyperglycemia, insulin resistance, hyperlipidemia and metabolic disease. Producing recombinant FGF21 by E. coli without using fusion proteins is time consuming and will produce low quantity products. In this study, to establish and test the efficiency of other expression methods, the complete fgf21 gene was constructed by overlapping PCR. The recombinant fgf21 genes were expressed successfully in E. coli (TB1) and in yeast (Pichia pastoris) under the control of maltose binding promoter and alcohol oxidase I promoter. The degree of success in terms of yield and functionality of the produced recombinant proteins in vivo were compared by using animal models. The result demonstrated that both expression systems can promote more soluble FGF21 levels, with less purification steps while preserving the bioactivity of the protein in vivo. The FGF21 produced in P. pastoris underwent post translation modification and was more active in lowering blood glucose compared with that in E. coli. The histologic effects of recombinant FGF21 (rFGF21) on Sprague Dawley adult rats reproductive systems were also investigated by focusing on the pattern changes and occurring differences after 28 days of treatment with rFGF21. A significant increase in the weight and size of organs in both genders were observed. Spermatogenesis in male and number of follicles and corpora lutea in female also in the treated group increased significantly compared to the controls. Further studies are needed to clarify the mechanism of action and the components responsible for these pharmacological effects.